Synthesis and Optical Characterization of Europium Doped MY2O4 (M = Mg, Ca, and Sr) Nanophosphors for Solid State Lightening Applications. (17th August 2015) - Singh, Devender; Tanwar, Vijeta; Bhagwan, Shri; Nishal, Vandna; Sheoran, Suman; Kadyan, Sonika; Samantilleke, Anura P.; Kadyan, Pratap Singh
Abstract : Trivalent europium doped yttriate nanophosphors were synthesized by rapid facile gel combustion technique. The photoluminescence (PL) properties of these Eu 3+ activated MY2 O4 (M = Mg, Ca, and Sr) nanophosphors showed red luminescence and exhibited excellent emission properties in their respective regions of color coordinates. Based on the excitation wavelengths multiple emission peaks were obtained. The main peak in the emission spectra was ascribed to 5 D0 → 7 F2 transition of Eu 3+ ion. The structural and morphological studies were performed by the measurements of X-ray diffraction profiles, scanning electron microscope (SEM) images, and transmission electron microscope (TEM) micrographs. Furthermore, the effects of additional heating on the different host lattices of these phosphors were also studied.